2021
DOI: 10.24002/ijis.v4i1.4338
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and the COVID-19: South African and Zimbabwean Netizens’ Response to a Pandemic

Abstract: Since the end of 2019, the world faced a major health crisis in the form of the Coronavirus (COVID-19) pandemic. To mitigate the impact of the pandemic, governments across the globe instituted measures such as restricting local and international travel and in many cases, ordering citizens to stay indoors. Considering the social and economic impact of these restrictions it becomes crucial to investigate internet citizens’ (netizens) perception about the precautionary measures adopted. The study is anchored in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…This is one example which helps to demonstrate how localised and globalised conspiracy narratives can be mutually reinforcing. 4 , 19 The same study 4 further shows that one of the events that generated a lot of interest on Twitter at the time was the pronouncement on television by French scientists Jean-Paul Mira and Camille Locht that the vaccine trials should be conducted on Africans. This saw a proliferation of comments on social media, especially from people of an African origin expressing their disappointment over the infamous proposal.…”
Section: Misinformation and Disinformation At Global Scale In A Publi...mentioning
confidence: 96%
See 2 more Smart Citations
“…This is one example which helps to demonstrate how localised and globalised conspiracy narratives can be mutually reinforcing. 4 , 19 The same study 4 further shows that one of the events that generated a lot of interest on Twitter at the time was the pronouncement on television by French scientists Jean-Paul Mira and Camille Locht that the vaccine trials should be conducted on Africans. This saw a proliferation of comments on social media, especially from people of an African origin expressing their disappointment over the infamous proposal.…”
Section: Misinformation and Disinformation At Global Scale In A Publi...mentioning
confidence: 96%
“…A study by Mutanga, Ureke, and Chani which used hashtags #COVID19SA, #CoronaVirusSA, #CoronaVirusZW, #Covid19Zim to evaluate the impact of social media in propagating the COVID-19 pandemic in South Africa and Zimbabwe has shown that international conspiracy scripts have increasingly been localized. 4 The study reveals that the words that featured prominently in tweets include “G5, “Vaccine”, “Africa”, “Bill Gates”, “Trust” and “microchip”. This is one example which helps to demonstrate how localised and globalised conspiracy narratives can be mutually reinforcing.…”
Section: Misinformation and Disinformation At Global Scale In A Publi...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note from the onset that the public sphere refers to an imagined space that exists between the state and civil society. This space normally provides a platform for rational and diverse debates among citizens on issues that are of common interest to them [19]. The public sphere therefore serves provides opportunities for discursive interaction, which could at times be very critical of the state or any critical occurrence in the society, such as the advent and spread of COVID-19 as in the context of this chapter.…”
Section: Theoretical Framework: Social Media As a Digital Public Spherementioning
confidence: 99%
“…As noted earlier on in this chapter, countries and governments across the globe immediately put in measures such as restricting local and international travel as local and international borders were closed in most cases. Additionally, most countries resort to various levels of regional and national lockdown by ordering their citizens to stay indoors to reduce the spread and impact of the pandemic [18,19]. There were fears, frustrations, and speculations among South Africans just like in other parts of the world, more so as there was a growing level of mistrust around the source of the virus, the likelihood of a cure and the rising death toll globally.…”
Section: Fake News and People's Perspectives On Covid-19mentioning
confidence: 99%